Analysis of the influence of synthetic paramaters on the structure and physico-chemical properties of non-spherical iron oxide nanocrystals and their biological stability and compatibility. Issue 2 (8th December 2015) - Pardo, Alberto; Pujales, Rosa; Blanco, Mateo; Villar-Alvarez, Eva M.; Barbosa, Silvia; Taboada, Pablo; Mosquera, Víctor
Abstract : Monodisperse non-spherical magnetic IONCs obtained by simple methods display excellent magnetic properties with high potential for theranostic applications. Abstract : In this work, we analyzed the effects of subtle changes in the synthetic conditions and synthetic parameters on the resulting size, shape, monodispersity, crystallinity and magnetic properties of iron oxide nanocrystals (IONCs) obtained through a modified one pot method for the production of mainly cubic-shaped nanoparticles (NPs). Cubic, octahedral and cuboctahedral shapes with different sizes and monodispersity could be obtained by slightly changing the stabilizer/precursor molar ratio, the precursor concentration, the reaction time and temperature and/or the heating rate. Their physical properties were evaluated using high-resolution transmission electron microscopy (HRTEM), X-ray powder diffraction (XRD), selected-area electron diffraction (SAED) and a superconducting quantum interference (SQUID) device. It was found that monodisperse cubic nanocrystals from ca. 25 to 94 nm could be obtained either by changing the precursor concentration, the heating rate or the reaction time. These cubic nanocrystals were ferrimagnetic in the whole temperature rage analyzed, with saturation magnetization values even larger than those of bulk magnetite. In addition, slightly truncated octahedral NPs could be achieved at relatively large heating ramp rates, whereas cubooctahedral NPs were derived by simply increasing the stabilizer/precursor molar ratio. The saturation magnetization of both types of NPs was slightly lower than the cubic ones, but they were still ferrimagnetic in the whole temperature range analyzed. Moreover, transfer to aqueous solution was possible by a ligand exchange with dimercaptosuccinic acid (DMSA) providing, at the same time, chemical groups for additional functionalization if required. The DMSA-coated cubic IONCs were fairly stable in culture medium, allowing their internalization by different cell types. The NPs inside the cells were located in the cytoplasm and most of them showed a perinuclear distribution. Moreover, a great cytocompatibility in a large range of particle concentrations was observed without the induction of morphological changes in the cultured cells.